Supplementary Diagnostic Landmarks of Left Ventricular Non-Compaction on Magnetic Resonance Imaging - Boban, Marko (Yonsei Med J, 2018)
PURPOSE: Diagnostic criteria for left ventricular non-compaction (LVNC) are still a matter of dispute. The aim of our present study was to test the diagnostic value of two novel diagnostic cardiac magnetic resonance (CMR) parameters: proof of non-compact (NC) myocardium blood flow using T2 sequences and changes in geometry of the left ventricle. MATERIALS AND METHODS: The study included cases with LVNC and controls, from a data base formed in a period of 3.5 years (n=1890 exams), in which CMR protocol included T2 sequences. Measurement of perpendicular maximal and minimal end diastolic dimensions in the region with NC myocardium from short axis plane was recorded, and calculated as a ratio (MaxMinEDDR), while flow through trabecula was proven by intracavital T2-weighted hyperintensity (ICT2HI). LVNC diagnosis met the following three criteria: thickening of compact (C) layer, NC:C>2.3:1 and NC>20%LV. RESULTS: The study included 200 patients; 71 with LVNC (35.5%; i.e., 3.76% of CMRs) and 129 (64.5%) controls. MaxMinEDDR in patients with LVNC was significantly different from that in controls (1.17±0.08 vs. 1.06±0.04, respectively; p<0.001). MaxMinEDDR >1.10 had sensitivity of 91.6% [95% confidence intervals (CI) 82.5–96.8], specificity of 85.3% (95% CI 78.0–90.0), and area under curve (AUC) 0.919 (95% CI 0.872–0.953; p<0.001) for LVNC. Existence of ICT2HI had sensitivity of 100.0% (95% CI 94.9–100.0), specificity of 91.5% (95% CI 85.3–95.7), and AUC 0.957 (95% CI 0.919–0.981; p<0.001) for LVNC. CONCLUSION: Two additional diagnostic parameters for LVNC were identified in this study. ICT2HI and geometric eccentricity of the ventricle both had relatively high sensitivity and specificity for diagnosing LVNC.